Quality of Translation for Post in Social media Facebook - Ika Oktaria Cahyaningrum (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2021)
The focus of this research is the quality of translation produced by Translation for Post on social media Facebook. As one of the social media with the most users, Facebook always improves its service features such as Market places, job vacancies, and even online games. One of the interesting things is a translation feature on Facebook, namely Translation for Post. After the researcher collected the data and analyzed it, there were 50% less accurate data and 70% less acceptable data. While for the quality of the readability, about 30% is included in the medium readability. Translation for Post is entered into the machine translator, so it is not surprising that there are vocabulary limitations or appropriate equivalents in the target language.